RANCANGAN PROJECT BASED E-LEARNING BERBASIS INTERNET OF THINGS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Wijaya, Elita Mega Selvia; Setiawan, Rudy (Universitas Insan Budi Utomo, 2023)
This research aims to improve the creative thinking abilities of Tribhuwana Tunggadewi University students through the use of an Internet of Things (IoT) based e-learning project design. The research subjects consisted of 60 students divided into experimental class (30 students) and control class (30 students). The research method used was a control class and an experimental class with pretest and posttest administration in both classes. The data collected is quantitative and qualitative data which is analyzed using descriptive and inferential statistical techniques. The research results showed that there was a significant difference between the creative thinking abilities of students in the experimental and control classes after being given treatment. The experimental class that used an IoT-based project-based e-learning design showed a more significant increase in creative thinking abilities compared to the control class. This shows that the use of IoT-based project based e-learning designs is effective in improving students' creative thinking abilities. Discussion of research results shows that the use of IoT-based project based e-learning designs can improve students' creative thinking abilities through more interactive, collaborative, and contextual learning. In addition, the use of IoT technology can facilitate student-centered learning activities and provide a more personalized and enjoyable learning experience. In conclusion, the use of an IoT-based project based e-learning design can be an innovative and effective alternative learning method in improving students' creative thinking abilities. This research contributes to the development of learning model that is oriented towards creative thinking skills and the use of technology in education.